Decoding the Digital Consumer How to Leverage Data Analytics to Skyrocket Sales - Tiana; Tiasih (Journal Bisnis Digital dan Inovasi Manajemen, 2026)
In the hyper-competitive digital marketplace, understanding evolving consumer behavior is paramount to business survival. While organizations generate vast amounts of transactional and behavioral data daily, many struggle to translate this raw information into actionable commercial strategies. This article explores how digital businesses can effectively leverage data analytics to decode consumer insights and optimize the digital customer journey. Employing a mixed-methods approach, this study analyzes data integration frameworks, predictive analytics models, and personalization tactics across various digital touchpoints. The findings reveal that companies utilizing advanced web and social analytics to personalize consumer experiences achieve significantly higher conversion rates and enhanced customer lifetime value (CLV). Ultimately, this paper provides a strategic framework for modern marketers and data analysts to convert data-driven insights into precise marketing execution, thereby systematically maximizing sales growth and brand loyalty in the digital economy.